The Influence of Village Apparatus Services on Community Satisfaction at the Karya Indah Village Office, Tapung District, Kampar Regency - Supriadi, Supriadi; Suryatunnisak, Suryatunnisak; Arfi, Lingga Ramadhana (Interconnection: An Economic Perspective Horizon, 2024)
This study aims to determine and analyze the influence of village apparatus services on community satisfaction. The analysis in this study uses a dependent variable, namely community satisfaction and an independent variable, namely village apparatus services. The research sample is the community of Karya Indah Village, Tapung District, Kampar Regency who provide services. The sampling technique is random sampling. The number of samples is 100 people. The results of the study show that the village apparatus service variable has a significant effect on the satisfaction of the community of Karya Indah Village, Tapung District, Kampar Regency. It is known that the t (count) value (9.475)> t (table) (1.984) and Sig. (0.00) <0.05, meaning that the village apparatus service variable has a significant effect on the satisfaction of the community of Karya Indah Village, Tapung District, Kampar Regency. The R Square value in this study is 0.706. This shows that there is a strong relationship between the independent variable and the dependent variable. The village apparatus service variable as a whole has an influence of 70.6% on the community satisfaction variable. While the remaining 29.4% is influenced by other variables not examined in this study.